2019
DOI: 10.2471/blt.18.216135
|View full text |Cite
|
Sign up to set email alerts
|

A decade of cigarette taxation in Bangladesh: lessons learnt for tobacco control

Abstract: Bangladesh has achieved a high share of tax in the price of cigarettes (greater than the 75% benchmark), but has not achieved the expected health benefits from reduction in cigarette consumption. In this paper we explore why cigarette taxation has not succeeded in reducing cigarette smoking in Bangladesh. Using government records over 2006–2017, we link trends in tax-paid cigarette sales to cigarette excise tax structure and changes in cigarette taxes and prices. We analysed data on smoking prevalence from Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“… 22 Third, countries subject to downward substitution to cheaper cigarettes in the presence of increasing prices may not see a decrease in sales or may even experience an increase in sales. 23 …”
Section: Resultsmentioning
confidence: 99%
“… 22 Third, countries subject to downward substitution to cheaper cigarettes in the presence of increasing prices may not see a decrease in sales or may even experience an increase in sales. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Taxation has been used to reduce the tobacco use epidemic, but results are inconclusive (7). A recent study in Bangladesh concluded that high tax share alone may not be a good measure of effective tobacco taxation in low-income countries, especially in countries with a complex tax arrangement, relatively cheap tobacco products and a growing affordability of tobacco products, which emphasizes the need for better and targeted health promotion activities (8). Although cigarette smoking has decreased in people under 18 years in the United States of America, the rate did not change from 2017 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh has been identified as a high-achieving country for several tobacco control measures, including tobacco taxation, health warning labels and anti-tobacco mass-media campaigns. The high level of achievement for Bangladesh in cigarette taxation is, however, contradicted by an increase in per capita cigarette consumption [57]. Urban male smokers in Bangladesh consume more cigarettes than bidis and smoke more per day than rural smokers.…”
Section: E Tobacco Smockingmentioning
confidence: 99%